Foxp3+ Regulatory T Cells Inhibit CCl4-Induced Liver Inflammation and Fibrosis by Regulating Tissue Cellular Immunity - Ikeno, Yoshinobu; Ohara, Daiya; Takeuchi, Yusuke; Watanabe, Hitomi; Kondoh, Gen; Taura, Kojiro; Uemoto, Shinji; Hirota, Keiji (Frontiers in Immunology, 2020)
Foxp3+ regulatory T (Treg) cells are pivotal in maintaining immunological self-tolerance and tissue homeostasis; however, it remains unclear how tissue Treg cells respond to liver injury and regulate chronic inflammation, which can cause liver fibrosis. We report here that hepatic Treg cells play a critical role in preventing liver pathology by suppressing inflammatory cellular immunity that can promote liver damage and fibrosis. Chronic liver inflammation induced by injections of carbon tetrachloride (CCl4) led to preferential expansion of hepatic Treg cells that prevented liver fibrosis. In contrast, depletion of Treg cells in the CCl4-induced liver fibrosis model exacerbated the severity of liver pathology. Treg depletion unleashed tissue cellular immunity and drove the activation and expansion of the pro-fibrotic IL-4-producing T helper 2 cells, as well as CCR2high Ly-6Chigh inflammatory monocytes/macrophages in the inflamed liver. Although Treg expression of amphiregulin plays a key role in tissue remodeling and repair in various inflammation models, amphiregulin from hepatic Treg cells, the largest producer among liver immune cells, was dispensable for maintaining liver homeostasis and preventing liver fibrosis during CCl4-induced chronic inflammation. Our results indicate that Treg cells control chronic liver inflammation and fibrosis by regulating the aberrant activation and functions of immune effector cells. Harnessing Treg functions, which effectively regulate tissue cellular immunity, may be a therapeutic strategy for preventing and treating liver fibrosis.